PENGARUH BUDAYA ORGANISASI DAN KETERLIBATAN KERJA TERHADAP KOMITMEN ORGANISASI (STUDI PADA PERAWAT RUMAH SAKIT JIWA TAMPAN PEKANBARU) - John Kennedy Sitopu; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to analyze organizational culture and work involvement and its effect on nurse organizational commitment at RSJ Tampan Pekanbaru. Organizational culture as a variable (X1), Job Involvement as a Variable (X2), and Organizational Commitment as a Variable (Y). The method in this study is descriptive and quantitative using the SPSS 23 program.the total population in this study was 127 nurses, the sample used was 56 respondents who choosen  by simple random sampling. Techniques for collecting data through questionnaires and interviews. The results of the analysis use validity test, t test and F test. So it can be concluded that organizational culture has a significant effect on nurse organizational commitment at RSJ Tampan Pekanbaru, work involvement has a significant effect on nurse organizational commitment at RSJ Tampan Pekanbaru, organizational culture and involvement work had a significant effect on nurses' organizational commitment at RSJ Tampan Pekanbaru. Keywords: Organizational Culture, Work Involvement, and Organizational                            Commitment